HOUT-29. THE INFLUENCE OF PSYCHIATRIC ILLNESS ON OUTCOME AND CANCER CARE RECEIVED IN PATIENTS WITH GLIOMAS. (11th November 2019) - Patel, Palak; Li, Terry; Chou, Janice; Patel, Amie; Crispino, Sylvia; Utate, Minerva; Kurz, Sylvia
Abstract: BACKGROUND: Data related to the prevalence of different psychiatric disorders and their impact on survival and compliance in patients with glioma is scarce and mostly anecdotal. We aimed to study the prevalence of psychiatric disorders in glioma patients and the possible influence on compliance with cancer care and outcome. METHODS: We performed a retrospective, observational study and compared compliance with medical care and outcome in patients who had or did not have a psychiatric illness at time of diagnosis. Kaplan-Meier method was used to compare survival between groups. RESULTS: We identified 22 subjects (M=13, F=9) with intracranial glioma with psychiatric diagnosis and 22 matched control subjects (M=13, F=9) without psychiatric illness. Psychiatric diagnoses included depression (12%), anxiety disorder (6%), Adjustment disorder & substance use problems (2% each), bipolar disorder (1%) and panic attacks (1%). Psychiatric diagnoses were predating tumor diagnosis in 9/22 (41%) subjects and occurred around tumor diagnosis in 11/22 (50%) patients. The time of diagnosis with psychiatric illness was unknown in 2/22 (9%) of cases. Tumor diagnoses were glioblastoma in 50%, anaplastic astrocytoma in 9%, anaplastic oligodendroglioma in 13%, oligodendroglioma in 4%, and astrocytoma in 9% of cases. MedianOS was not reached for cases with psychiatric illness (not reached due to censoring) but was 4.2 years (95% CI 1.1 – 7.4) in controls (p=0.263). Subjects with psychiatric illness had an increased risk (OR 7.5, 95% CI 0.81 -68.8) of poor compliance with cancer care (medication, clinic and MRI follow-up compliance) compared to controls (p=0.046). CONCLUSION: A variety of psychiatric conditions were observed in patients with glioma and presence of psychiatric illness may influence compliance with treatment and follow-up. Studies with larger population and longer follow-up are warranted to clarify true association between psychiatric conditions and compliance and survival.